Design and simulation of hydraulic shaking table - Ngadimon, Khairulnizam (2006)
Recent industrial progress and computational technology made it possible to construct more complex structures. Vibration of these structures due to seismic strength must be measured and proved to prevent them from damage when they arc subjected to earthquake. However, the accuracy of estimating the effect of vibrating structures is limited by the mathematical models, which are normally simplified from the actual complex structures. Due to this problem, a study on the development of shaking table is proposed. The main purpose of this study is to obtain the design specifications for a 1-axis (horizontal) hydraulic shaking table with medium loading, which can function primarily as an earthquake simulator and a dynamic structural testing apparatus. The project employs a three stage electrohvdraulic servovalvc. actuator system complete with hydraulic system as the power and drive unit. Mathematical model for closed loop control experimentation was presented and used to investigate the influence of various parameters on the overall system. The investigation includes the study on the effect of controller gain setting (for PD and AFC), disturbances and system stability. Time domain analysis using computer simulation was conducted to explain and predict the system's response. Comparison between PD and PD-AFC controllers was done and it was found that latter PD-AFC fulfills the performance and robustness specifications for this project. Other design outcome that limits the change of disturbances on the system was also identified and taken as the framework for real world. This suggests that the next stage in implementation of the designed system can be made for the purpose of an earthquake simulator, since it works very well especially at low frequency level of shaking (0 to 5 Hz).